The classical music lover's companion to orchestral music - Philip, Robert, 1945- (Yale University Press, 2018)
Robert Philip, scholar, broadcaster, and musician, has compiled an essential handbook for lovers of classical music, designed to enhance their listening experience to the full. Covering four hundred works by sixty-eight composers from Corelli to Shostakovich, from 1700 to 1950, this engaging companion explores and unpacks the most frequently performed works, including symphonies, concertos, overtures, suites, and ballet scores. It offers intriguing details about each piece while avoiding technical terminology that might frustrate the non-specialist reader. Philip identifies key features in each work, as well as subtleties and surprises that await the attentive listener, and he includes enough background and biographical information to illuminate the composer's intentions. Organized alphabetically from Bach to Webern, this compendium will be indispensable for classical music enthusiasts, whether in the concert hall or enjoying recordings at home.